The European Monetary System in the Context of the integration of European Financial Markets : Occa Paper No.66. (Occasional Papers; Occasional Paper ;, 1989)
This paper provides a survey of some issues concerning the evolution of the European Monetary System (EMS) in the context of increasingly integrated financial markets. It reviews the objectives of the EMS, its institutional structure, its perceived impact on key macroeconomic variables, and some criticisms of its current arrangements. It also describes the 1992 program to unify, inter alia, financial markets and then discusses the pressures that a more integrated financial marketplaces on country authorities and on financial firms. The prospective structural changes in European financial markets raise the issues of whether and how the EMS can continue to constitute a zone of monetary stability. Although the growing integration of financial markets is likely to increase the interdependence between monetary policies in the EMS countries, a nominal anchor could still be maintained by having the Bundesbank continue to lead the way on the course of monetary policy, or by formulating monetary policy on the basis of an index of traded goods prices, or through more far-ranging coordination of monetary policies.